Associated ACL risk factors differences during an unanticipated volleyball blocking movement - Zahradnik, D.; Jandacka, D.; Beinhauerova, G.; Hamill, J. (Journal of Sports Sciences, 2020)
The lateral tilt of the arms accompanied by trunk lateral tilt is a typical blocking manoeuvre in volleyball. However, during this unanticipated blocking movement, an associated risk of ACL injury may result. The aim of the present study was to compare associative ACL risk factors at the initial contact and the first and second peak of VGRF during an unanticipated blocking movement with different arm positions. Synchronized kinematic and kinetic data were collected for each trial of each condition. Student paired t-tests and effect size were used to determine differences between two conditions (S - with arms straight up from the body) and (T - with the arms and trunk laterally tilted). The results showed that the T condition significantly decreases knee flexion, increases VGRF at the foot contact, first peak force and increases the valgus moment at the first peak force. The values of the associated risk factors for a non-contact ACL injury appear to be related to the tilted arm position accompanied by trunk tilt towards to right lower limb during landing. The players should be taught to land with greater knee flexion and, if possible, a double-leg landing to decrease right lower limb loading during the blocking manoeuvre.